Alternative cause for hypoglycaemia in insulin-treated diabetes mellitus. Issue 7 (23rd July 2021) - Parmar, Viraj; Sritharan, Vasanth; Lawrence, Christopher; Dhere, Archana
Abstract : We present a case of a 73-year-old woman who developed recurrent hypoglycaemia during a prolonged hospital stay following a mechanical fall. She had a complex history of insulin-treated diabetes mellitus, hypothyroidism, diffuse systemic cutaneous sclerosis, Raynaud's disease, previous breast cancer, Barrett's oesophagus and previous partial gastrectomy for a benign mass. Hypoglycaemia persisted despite weaning of insulin. She had no clinical features of adrenal or pituitary insufficiency with an acceptable cortisol on stopping prednisolone and had an optimal thyroid replacement. A 72-hour fast elicited hypoglycaemia with corresponding low insulin level. Although the C-peptide was detectable, there were no clinical, biochemical or radiological features suggestive of insulinoma. Reactive hypoglycaemia post partial gastrectomy was ruled out based on limited relation of the hypoglycaemia to meals and the low insulin levels. Hydroxychloroquine (HCQ)-induced hypoglycaemia was considered based on previous case reports and the recent literature, with a successful resolution of hypoglycaemia on discontinuation of HCQ.